Synthesis, Characterization and Antimicrobial Activity of Metal Chelates of 5-[4-(3-Chloro phenyl)piperazinylmethylene]- 8-hydroxy Quinoline - PATEL, I.J.; VHORA, I.M. (Asian Journal of Chemistry, 2010)
5-Chloro methyl-8-quinolinol was condensed with 4-3(3-chloro phenyl piperazine in presence of sodium bicarbonate. The resulting 5-[4-(3-chloro phenyl)piperazinyl methylene]-8-quinolinol (CPPQ) was characterized by elemental analysis and spectral studies. The transition metal chelates viz., Cu2+, Ni2+, Co2+, Mn2+, Zn2+ and Cd2+ of CPPQ were prepared and characterized by metal-ligand (M:L) ratio, IR and reflectance spectroscopies and magnetic properties. The antifungal activity of CPPQ and its metal chelates was screened against various fungi. The results show that all these samples are good antifungal agents.